Cell-Based HIF1α Gene Therapy Reduces Myocardial Scar and Enhances Angiopoietic Proteome, Transcriptomic and miRNA Expression in Experimental Chronic Left Ventricular Dysfunction - Gara, Edit; Ong, Sang-Ging; Winkler, Johannes; Zlabinger, Katrin; Lukovic, Dominika; Merkely, Bela; Emmert, Maximilian Y.; Wolint, Petra; Hoerstrup, Simon P.; Gyöngyösi, Mariann; Wu, Joseph C.; Pavo, Noemi (Frontiers in Bioengineering and Biotechnology, 2022)
Recent preclinical investigations and clinical trials with stem cells mostly studied bone-marrow-derived mononuclear cells (BM-MNCs), which so far failed to meet clinically significant functional study endpoints. BM-MNCs containing small proportions of stem cells provide little regenerative potential, while mesenchymal stem cells (MSCs) promise effective therapy via paracrine impact. Genetic engineering for rationally enhancing paracrine effects of implanted stem cells is an attractive option for further development of therapeutic cardiac repair strategies. Non-viral, efficient transfection methods promise improved clinical translation, longevity and a high level of gene delivery. Hypoxia-induced factor 1α is responsible for pro-angiogenic, anti-apoptotic and anti-remodeling mechanisms. Here we aimed to apply a cellular gene therapy model in chronic ischemic heart failure in pigs. A non-viral circular minicircle DNA vector (MiCi) was used for in vitro transfection of porcine MSCs (pMSC) with HIF1α (pMSC-MiCi-HIF-1α). pMSCs-MiCi-HIF-1α were injected endomyocardially into the border zone of an anterior myocardial infarction one month post-reperfused-infarct. Cell injection was guided via 3D-guided NOGA electro-magnetic catheter delivery system. pMSC-MiCi-HIF-1α delivery improved cardiac output and reduced myocardial scar size. Abundances of pro-angiogenic proteins were analyzed 12, 24 h and 1 month after the delivery of the regenerative substances. In a protein array, the significantly increased angiogenesis proteins were Activin A, Angiopoietin, Artemin, Endothelin-1, MCP-1; and remodeling factors ADAMTS1, FGFs, TGFb1, MMPs, and Serpins. In a qPCR analysis, increased levels of angiopeptin, CXCL12, HIF-1α and miR-132 were found 24 h after cell-based gene delivery, compared to those in untreated animals with infarction and in control animals. Expression of angiopeptin increased already 12 h after treatment, and miR-1 expression was reduced at that time point. In total, pMSC overexpressing HIF-1α showed beneficial effects for treatment of ischemic injury, mediated by stimulation of angiogenesis.